2019
DOI: 10.3390/s19163568
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Multi-Position Calibration Method with Nonlinear Scale Factor for Inertial Measurement Units

Abstract: Navigation grade inertial measurement units (IMUs) should be calibrated after Inertial Navigation Systems (INSs) are assembled and be re-calibrated after certain periods of time. The multi-position calibration methods with advantage of not requiring high-precision equipment are widely discussed. However, the existing multi-position calibration methods for IMU are based on the model of linear scale factors. To improve the precision of INS, the nonlinear scale factors should be calibrated accurately. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…We can deduce from Figure 6, that α ij is best estimated if the rotation axis j is horizontal and the rotated axis i (see Figure 3) forms a ±50 or ±150 gon angle with the gravity vector. These findings match the conclusions from Reference [38], who did this investigations prior to their estimation process.…”
Section: Improvement Strategysupporting
confidence: 90%
“…We can deduce from Figure 6, that α ij is best estimated if the rotation axis j is horizontal and the rotated axis i (see Figure 3) forms a ±50 or ±150 gon angle with the gravity vector. These findings match the conclusions from Reference [38], who did this investigations prior to their estimation process.…”
Section: Improvement Strategysupporting
confidence: 90%
“…The single-axis RINS consists of a tri-axis fiber optic gyroscope, and tri-axis quartz accelerometer with precisions of 0.01 • /h and 0.01 mg respectively. Firstly, the thermal calibration was performed based on the traditional method and the two proposed methods, then the IMU calibration was done based on our previous work [29] to transform the pulse output into the rotation rate and specific force.…”
Section: Thermal Calibration and Verification Experimentsmentioning
confidence: 99%
“…In essence, IMU calibration technology is the process of optimizing the calibration parameters in the calibration model, so the selection of the mathematical model will directly affect calibration result. In order to improve the calibration accuracy, the second-order nonlinear scale factor [16] is introduced into the calibration model in this paper:…”
Section: Calibration Model Of Triaxial Accelerometermentioning
confidence: 99%
“…Different from the research of Ye et al, in 2019, Wang et al developed a calibration method for the IMU with a nonlinear mathematical model. This method could get high calibration accuracy by Levenberg-Marquardt (LM) optimization algorithm, but the mathematical model which it used is too complicated [16]. To sum up, it can be found that the optimization algorithm, as a common method for processing data and optimizing indicators [17,18], is now widely used in sensor calibration.…”
Section: Introductionmentioning
confidence: 99%